Postcoloniality The French Dimension - Majumdar, Margaret A. (Berghahn Books, 2007)
Postcolonial theory is central to many scholarly debates around the world. Some of these debates have become rather sterile and are characterized by a repetitive reworking of old issues, focusing on cultural questions of language and identity in particular. Margaret A. Majumdar investigates the causes of the apparent stagnation of postcolonial theory in some circles, and provides an overview of the divergence between Anglophone and Francophone approaches to the postcolonial. Outlining in particular the contribution of thinkers such as Césaire, Senghor, Memmi, Sartre and Fanon to the worldwide development of anti-imperialist ideas, she offers a critical perspective on the ongoing difficulties of France's relationship with its colonial and postcolonial Others and suggests new lines of thought that are currently emerging in the Francophone world, which are sure to enliven Anglophone discussion and debates.